2018
DOI: 10.1111/gcb.14114
|View full text |Cite
|
Sign up to set email alerts
|

Population collapse dynamics in Acropora downingi, an Arabian/Persian Gulf ecosystem‐engineering coral, linked to rising temperature

Abstract: As in the tropical Atlantic, Acropora populations in the southern Persian/Arabian Gulf plummeted within two decades after having been ecosystem engineers on most wave-exposed reefs since the Pleistocene. Since 1996/1998 live coral cover in the Gulf declined by over 90% in many areas, primarily due to bleaching and diseases caused by rising temperatures. In the formerly dominant table-coral species A. downingi, population dynamics corresponding to disturbance regimes was quantified in three transition matrices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 94 publications
(184 reference statements)
1
59
0
Order By: Relevance
“…Corals in the Gulf are known to be genetically adapted to the unusually extreme conditions that characterize the region (Howells et al, 2016;Smith et al, 2017;Kirk et al, 2018), but it is not absolute temperatures that induce bleaching; rather it is a departure from the typical mean summer temperature in which these coral populations have evolved. Mean SSTs in the Gulf have been increasing over the past three decades as a result of climate change (Riegl et al, 2011), and as a result there has been an increase in the frequency and magnitude of mass bleaching events where corals have been being pushed beyond their thermal limits (Riegl et al, 2018). Severe bleaching leading to widespread mass coral die-off 's (>80% loss) was first reported in the late 1970s, then again in 1996, 1998, and 2017, with slight to moderate bleaching events that resulted in more limited coral mortality (0∼20% loss) also occurring in 2002, 2010, 2011, and 2012 (Sheppard and Loughland, 2002;Riegl and Purkis, 2015;Shuail et al, 2016;Riegl et al, 2018;Burt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corals in the Gulf are known to be genetically adapted to the unusually extreme conditions that characterize the region (Howells et al, 2016;Smith et al, 2017;Kirk et al, 2018), but it is not absolute temperatures that induce bleaching; rather it is a departure from the typical mean summer temperature in which these coral populations have evolved. Mean SSTs in the Gulf have been increasing over the past three decades as a result of climate change (Riegl et al, 2011), and as a result there has been an increase in the frequency and magnitude of mass bleaching events where corals have been being pushed beyond their thermal limits (Riegl et al, 2018). Severe bleaching leading to widespread mass coral die-off 's (>80% loss) was first reported in the late 1970s, then again in 1996, 1998, and 2017, with slight to moderate bleaching events that resulted in more limited coral mortality (0∼20% loss) also occurring in 2002, 2010, 2011, and 2012 (Sheppard and Loughland, 2002;Riegl and Purkis, 2015;Shuail et al, 2016;Riegl et al, 2018;Burt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mean SSTs in the Gulf have been increasing over the past three decades as a result of climate change (Riegl et al, 2011), and as a result there has been an increase in the frequency and magnitude of mass bleaching events where corals have been being pushed beyond their thermal limits (Riegl et al, 2018). Severe bleaching leading to widespread mass coral die-off 's (>80% loss) was first reported in the late 1970s, then again in 1996, 1998, and 2017, with slight to moderate bleaching events that resulted in more limited coral mortality (0∼20% loss) also occurring in 2002, 2010, 2011, and 2012 (Sheppard and Loughland, 2002;Riegl and Purkis, 2015;Shuail et al, 2016;Riegl et al, 2018;Burt et al, 2019). Recent work has shown that it is not the maximum temperature so much as the length of exposure that affects the severity of bleaching and whether or not mass mortality occurs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the southern Persian (Arabian) Gulf is home to the hottest coral ecosystems in the world, where daily average summer seawater temperatures are >34-35℃, and are lethal for corals elsewhere (Riegl, Purkis, Al-Cibahy, Abdel-Moati, & Hoegh-Guldberg, 2011). Gulf corals live exceptionally close to their upper thermal limits (Howells, Abrego, Meyer, Kirk, & Burt, 2016) and undergo repeated episodes of heat stress (Riegl et al, 2018). They also experience large shifts in temperature across seasons (~16℃) and hypersaline conditions (40-42 PSU [practical salinity unit]; Bauman, Feary, Heron, Pratchett, & Burt, 2013).…”
mentioning
confidence: 99%
“…Indeed, Pomacentrus trichrourus are highly associated with live coral colonies, utilising them for recruitment, shelter and as trophic resources (Buchanan et al 2016; Shraim et al 2017). Therefore, any increases in SST that pose a serious threat to local coral communities, where bleaching events and consequent coral mortality are already common (Riegl and Purkis 2015; Riegl et al 2018), may deprive P. trichrourus populations of suitable habitat and food resources (Keith et al 2018; Pratchett et al 2018).…”
Section: Discussionmentioning
confidence: 99%